High Abundance of Intratumoral γδ T Cells Favors a Better Prognosis in Head and Neck Squamous Cell Carcinoma: A Bioinformatic Analysis - Lu, Huanzi; Dai, Wenxiao; Guo, Junyi; Wang, Dikan; Wen, Shuqiong; Yang, Lisa; Lin, Dongjia; Xie, Wenqiang; Wen, Liling; Fang, Juan; Wang, Zhi (Frontiers in Immunology, 2020)
γδ T cells are a small subset of unconventional T cells that are enriched in the mucosal areas, and are responsible for pathogen clearance and maintaining integrity. However, the role of γδ T cells in head and neck squamous cell carcinoma (HNSCC) is largely unknown. Here, by using RNA-seq data from The Cancer Genome Atlas (TCGA), we discovered that HNSCC patients with higher levels of γδ T cells were positively associated with lower clinical stages and better overall survival, and high abundance of γδ T cells was positively correlated with CD8+/CD4+ T cell infiltration. Gene ontology and pathway analyses showed that genes associated with T cell activation, proliferation, effector functions, cytotoxicity, and chemokine production were enriched in the group with a higher γδ T cell abundance. Furthermore, we found that the abundance of γδ T cells was positively associated with the expression of the butyrophilin (BTN) family proteins BTN3A1/BTN3A2/BTN3A3 and BTN2A1, but only MICB, one of the ligands of NKG2D, was involved in the activation of γδ T cells, indicating that the BTN family proteins might be involved in the activation and proliferation of γδ T cells in the tumor microenvironment of HNSCC. Our results indicated that γδ T cells, along with their ligands, are promising targets in HNSCC with great prognostic values and treatment potentials.